The Journal “Tabor” (1923–1939): Thematic palette and information potential of publications, role in the consolidation of Ukrainian military emigration in Poland - Maciej Krotofil; Ihor Sribnyak; Natalia Yakovenko (Київські історичні студії)
The article reveals key aspects of the history of the publication of the military-historical journal “Tabor”, which was founded in the camp of interned Ukrainian soldiers in Kalisz (Poland) in 1923 by a group of generals and senior officers of the Army of the Ukrainian People’s Republic. Among its co-creators was the chief ataman Symon Petliura, who prepared an article for its first issue, which formulated programmatic objectives for the entire Ukrainian military emigration. From the beginning of the publication, the vast majority of articles were devoted almost exclusively to military topics, but starting in 1927, the journal began to include materials of various genres of an ideological, political, and polemical nature, united by the idea of restoring the UРR. At this time, the journal received a significant financial subsidy from a special account of the General Staff of the Polish Army, which allowed it to pay royalties and improve the publication’s printing. In total, by 1939, 37 issues of the journal were published, which included articles by famous military figures of the UРR Army, memoir materials, information with an analysis of the political situation, etc. During this time, the journal became one of the important centers for the development of Ukrainian military theoretical thought and a center for uniting Ukrainian combatants. The importance of researching this topic lies in introducing the materials of the journal “Tabor” into scientific circulation, as well as determining the degree of its organizational influence on Ukrainian combatants. The aim of the article is to reconstruct the main milestones in the publishing history of the journal “Tabor”, to establish the circle of its most active employees from among the leading representatives of the Ukrainian military emigration, as well as to outline the contribution of the Polish military authorities to ensuring the circulation of the aforementioned journal.